Zika Virus Circulates at Low Levels in Western and Coastal Kenya. (6th May 2020) - Gobillot, Theodore A; Kikawa, Caroline; Lehman, Dara A; Kinuthia, John; Drake, Alison L; Jaoko, Walter; Mandaliya, Kishorchandra; John-Stewart, Grace; McClelland, R Scott; Overbaugh, Julie
Abstract: Background: Zika virus (ZIKV) was discovered over 70 years ago in East Africa, but little is known about its circulation and pathogenesis there. Methods: We screened 327 plasma samples collected 2–12 months after febrile illness in Western and coastal Kenya (1993–2016) for binding and neutralizing antibodies to distinguish ZIKV and dengue virus (DENV) responses, which we found were common in coastal Kenya. Results: Two cases had durable ZIKV-specific antibodies and 2 cases had ZIKV antibodies at similar levels as DENV antibodies. Conclusions: This suggests low-level ZIKV circulation in Kenya over 2 decades and sets a baseline for future surveillance efforts in East Africa. Abstract : Four cases of Zika virus infection were identified by screening 327 convalescent plasma samples collected from individuals who experienced Zika-like illness in 2 urban regions of Kenya, suggesting a low burden of Zika infections in Kenya over a 20-year period.